A SHRIMP II Ion Microprobe at the Geological Survey of Canada - Stern, Richard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Early in 1996, the Geological Survey of Canada acquired a Sensitive High-Resolution Ion Microprobe (SHRIMP). Now operating, this instrument permits precise in situ measurement of isotopes in mineral grains. SHRIMP complements the widely used isotopic dating method of isotope dilution thermal ionization mass spectrometry. Although SHRIMP is less precise than isotope dilution methods, the material sampled is much smaller, offering better spatial resolution and faster analysis. SHRIMP'S most important application is the determination of U-Pb isotopic ages of zircon. Studies particulary suited to SHRIMP include analysis of minerals in situ where context is vital (e.g., complex metamorphicrocks), detrital zircon chronology in sedimentary basin analysis, and reconnaissance zircon chronology with application to geological mapping and mineral exploration projects. SHRIMP will be accessible to academia/industry researchers in Canada in late 1996, following development of requisite analytical/scientific expertise.